HUBUNGAN DUKUNGAN SOSIAL SUAMI DENGAN KEPUASAN PERNIKAHAN PADA IBU BEKERJA SEBAGAI PERAWAT DI KOTA MAKASSAR - Rahmah, Tri; Nur, Haerani; Ansar, Wilda (Polteknik Ilmu Pemasyarakatan, 2023)
Working mothers undergo role demands between family and work which can lead to an imbalance of roles. Role imbalance has an impact on marital satisfaction in working mothers. The purpose of this study was to determine the relationship between husband's social support and marital satisfaction of mothers working as nurses in Makassar City. The subjects in this study were 103 respondents with the characteristics of working mothers, nursing profession, living with their husbands, and having children aged 1-12 years. The sampling technique uses purposive sampling. This study uses the marital satisfaction scale and the social support scale. The results of hypothesis testing using the Pearson product moment correlation showed a significance value of p = 0.00 <0.05 so that the hypothesis in this study was accepted. The results of this study indicate that there is a significant relationship between husband's social support and marital satisfaction in mothers working as nurses in Makassar City. In addition, the correlation coefficient value shows a value of 0.847 in a positive direction. This shows that the higher the husband's social support, the higher the marital satisfaction for mothers working as nurses, and vice versa. The implication of this research is to reflect on the general public regarding the importance of social support, especially from husbands, to increase marital satisfaction for mothers who work as nurses.